Front cover: Bitcoin address clustering method based on multiple heuristic conditions. Issue 2 (22nd June 2022) - Unknown
Abstract : The cover image is based on the Original Research Bitcoin address clustering method based on multiple heuristic conditions by Xi He et al., https://doi.org/10.1049/blc2.12014 .